Rechtsstaat from the Perspective of Al-Ghazali and Ibn Khaldun - Rusli, Ris'an; Wijaya; Azwar, Alfi Julizun; Utami, Devi Aulia (NAJAHA, 2025)
The concept of a state is a closely related discourse to the lives of all humanity. However, the Holy Quran and Hadits, as guidance for Muslims, did not mention the specific form and concept of a state. Therefore, this paper will discuss the idea of a state from some Islamic intellectual perspectives, such as al-Ghazali and Ibn Khaldun. Both of them were trying to formulate the form and concept of the state. This article uses a qualitative research method with a type of library research. This type of research allows primary data sources to come from books authored by Al-Ghazali and Ibn Khaldun. At the same time, secondary data sources come from various articles and other scientific books that can support the author's arguments. To analyze their thought, this article uses comparative analysis; comparative analysis allows researchers to understand how the two thinkers view the concept of the state of law and how their thinking can be compared in different contexts. The results of the study show that Al-Ghazali and Ibn Khaldun have similarities in emphasizing the relationship between region and politics, as well as the importance of religious principles in government. They agreed that the government must maintain order and justice. However, the difference lies in the approach and form of government; Al-Ghazali supported the monarchy, while Ibn Khaldun did not specify a specific form as long as it met the criteria for justice. Their thinking can be the basis for understanding the interaction of religion and politics in creating a just system of government. Nevertheless, this paper is limited to the views of Ghazali and ibn Khaldun to understand the thoughts of both without involving experimental empirical methods.